Religiosity and consumer behaviour: A study of consumer preferences and well-being among younger and older Malaysians - Fon Sim Ong (2018)
This paper examines the relationship between religiosity and two concepts of interest to consumer researchers: consumer well-being and consumer preferences. Our study replicates and extends previous research on cultural and subcultural influences on consumer well-being and consumer preferences, in an attempt to understand the reasons for the previously uncovered relationships between religiosity and our focus variables. The present study was based on a government-funded large-scale survey using the faceto- fact interviews with 1,025 respondents in Malaysia. The results suggest the positive effect of religiosity on well-being as found in past studies. Regardless of age, Malaysians who are more religious tend to exhibit stability in preferences suggesting that religious people are more dogmatic compared to their less religious counterparts. The mediating role of religiosity on the relationship between age and well-being was not supported. Marketing implications, limitations and directions for future research are suggested.